CURENT TRENDS IN FLOOD RISK MANAGEMENT (LEGAL ASPECTS) - Nikolić Popadić, Sofija D. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Directive 2000/60/EC of the European Parliament and of the Council of 23 October 2000 establishing a framework for Community action in the field of water policy and Directive 2007/60/EC of the European Parliament and of the Council of 23 October 2007 on the assessment and management of flood risks are basic regulations at the level of the European Union in the field of flood protection. Serbia is in the process of harmonization of legal regulations in this area. The paper analyzes three phases of flood management envisaged by the Floods Directive, as well as their application in some European countries and Serbia. The current problems that have arisen in the implementation process are considered. Special emphasis is on the issues related to the development and implementation of flood hazard maps and flood risk maps and practices of different countries regarding their use, particularly in the field of spatial and urban planning and insurance. It is currently uncertain what would be the consequences of the application of these maps in Serbia. The question is to what extent and in which areas they will be used, whether they will influence the restriction of the construction in risk zones, would they affect the value of real estates in certain areas, would they be integrated into the real estate register, and what impact they will have in the field of insurance.